DEM Study of Wet Cohesive Particles in the Presence of Liquid Bridges in a Gas Fluidized Bed. (4th June 2014) - He, Yurong; Peng, Wengen; Wang, Tianyu; Yan, Shengnan
Abstract : A modified discrete element method (DEM) was constructed by compositing an additional liquid-bridge module into the traditional soft-sphere interaction model. Simulations of particles with and without liquid bridges are conducted in a bubbling fluidized bed. The geometry of the simulated bed is the same as the one in Müller's experiment (Müller et al., 2008). A comparison between the dry and the wet particular systems is carried out on the bubble behavior, the bed fluctuation, and the mixing process. The bubble in the dry system possesses a regular round shape and falling of scattered particles exists while the bubble boundary of the wet particles becomes rough with branches of agglomerates stretching into it. The mixing of the dry system is quicker than that of the wet system. Several interparticle liquid contents are applied in this work to find their influence on the kinetic characteristic of the wet particle flow. With an increase of liquid content, the mixing process costs more time to be completed. Symmetrical profiles of the velocity and granular temperature are found for two low liquid contents (0.001% and 0.01%), while it is antisymmetrical for the highest liquid content (0.1%).